TRUSTEESHIP IN WARRANTY - Mávila H., Daniel (2002)
According to a survey performed by the Banco Interamericano de Desarrollo (BID) in June 2002, Peru holds the last position in the Credit Protection Leveis in Latin America's ranking, a fact which to a greater extent explains the lack of credit in our country. Guarantees required by the money-lender have no protection measures for quickly recovering the loan; an alternative for this is the Guarantee Trusteeship, which is the subject of the present research.